2009
DOI: 10.1007/s00213-008-1451-x
|View full text |Cite
|
Sign up to set email alerts
|

Timing and space usage are disrupted by amphetamine in rats maintained on DRL 24-s and DRL 72-s schedules of reinforcement

Abstract: Rationale A differential-reinforcement-of-low-rate schedule (DRL) delivers reinforcement only when the interresponse time (IRT) exceeds a fixed time interval, thereby shaping rats to discriminate the timing of their responses. However, little is known about the motor behavior and location of the rats in the chamber during the IRTs that lead to reinforcement. Although amphetamine is known to disrupt DRL timing behavior, the effects of this drug on non-operant motor behavior during DRL performance has not yet be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…If this were true, increased premature responding could simply be an exacerbation of the normal, anticipatory responses we observed in the Fixed 4-s condition. In agreement with this idea, amphetamine increases premature responses in other tasks with consistent delays, such as the 5-CSRTT (Cole and Robbins, 1987;Harrison et al, 1997;van Gaalen et al, 2006) and DRL tasks (Seiden et al, 1979;Lobarinas and Falk, 1999;Bizot 1998;Fowler et al, 2009), but not in the stop task which uses a variable delay to the signal for RI (Feola et al, 2000;Eagle and Robbins, 2003). Disruptions in timing abilities would not affect performance in the Variable condition, so it is not surprising that we failed to observe an amphetamine-induced increase in impulsive action in this version of the task.…”
Section: Amphetamine-induced Changes In Impulsive Action May Interactsupporting
confidence: 74%
See 2 more Smart Citations
“…If this were true, increased premature responding could simply be an exacerbation of the normal, anticipatory responses we observed in the Fixed 4-s condition. In agreement with this idea, amphetamine increases premature responses in other tasks with consistent delays, such as the 5-CSRTT (Cole and Robbins, 1987;Harrison et al, 1997;van Gaalen et al, 2006) and DRL tasks (Seiden et al, 1979;Lobarinas and Falk, 1999;Bizot 1998;Fowler et al, 2009), but not in the stop task which uses a variable delay to the signal for RI (Feola et al, 2000;Eagle and Robbins, 2003). Disruptions in timing abilities would not affect performance in the Variable condition, so it is not surprising that we failed to observe an amphetamine-induced increase in impulsive action in this version of the task.…”
Section: Amphetamine-induced Changes In Impulsive Action May Interactsupporting
confidence: 74%
“…That is, even though the length of the delay interval was predictable, subjects did not exhibit anticipatory responding toward the end of the interval. It is unlikely that the difference in these two patterns reflects an ability to time short (4 s) but not long (60 s) intervals as rats responding under DRL schedules can accurately assess delays of the longer duration (Seiden et al, 1979;Lobarinas and Falk, 1999;Bizot 1998;Fowler et al, 2009). The DRL task differs from the fixed delay version of the RI task in that the delay period in the latter is signaled.…”
Section: Expectation Of Delay Duration Alters the Probability Of Impumentioning
confidence: 99%
See 1 more Smart Citation
“…Independent laboratories have replicated amphetamineinduced impulsivity for the 5-CSRTT (Pattij et al, 2007;Paterson et al, 2011b;Baarendse and Vanderschuren, 2012). For DRL 72-second behavior, amphetamine-induced increases in impulsivity have been suggested by increased response rates and cohesive leftward shift in the IRT distribution, including decreased peak latency (Balcells-Olivero et al, 1998;Fowler et al, 2009;Paterson et al, 2011a).…”
Section: Rethinking An Empirical Antidepressant Screenmentioning
confidence: 99%
“…The shape of the IRT distribution means that usually less than 15% of total lever presses are followed by availability of a water (or food) reinforcer. Under control conditions, Fowler et al (2009) have suggested that rats responding on a DRL 72-second schedule locate themselves away from the operant lever and tend to exhibit very little movement. Only in the approximately last 8 seconds prior to a reinforced or unreinforced response did the rats exhibit an increased amount of horizontal locomotion.…”
Section: Introductionmentioning
confidence: 99%